2020
DOI: 10.1016/j.neuron.2019.10.008
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic Restriction of Network Dynamics Regulates Interneuron Survival in the Developing Cortex

Abstract: Highlights d GABA limits MGE-cIN participation in synchronous network events during development d Synaptic GABA regulates the emergence of interneuronpyramidal cell assemblies d GABAergic restriction of pyramidal cell activity is required for MGE-cIN apoptosis d GABA A g2-containing GABA A receptors are essential for interneuron apoptosis Authors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 83 publications
6
91
1
Order By: Relevance
“…Brain cells undergo massive elimination during two waves of apoptosis that take place from the embryonic stage E14 and between P6 and P10 in mice ( Figure 2 ; for review Wong and Marin, 2019 ). In contrast to previously reported cell-autonomous regulation of cell death (Southwell et al, 2012 ), new evidence suggests that specific patterns of postnatal network activity establish the onset, duration and extent of neuronal apoptosis (Blanquie et al, 2017 ; Denaxa et al, 2018 ; Priya et al, 2018 ; Wong et al, 2018 ; Duan et al, 2020 ). Recent work identified two molecular pathways guiding the selection process that determines neuron survival and sets the final composition of a neural network in the cerebral cortex: the calcium-dependent phosphatase Calcineurin, that translates the arrival of electrical activity into molecular cascades of cell survival (Priya et al, 2018 ), and the phosphatase tensin homolog protein (PTEN), that sets the clock for the death of the GABAergic interneurons in the absence of incoming activity from pyramidal neurons (Wong et al, 2018 ).…”
Section: Classical Critical Periods and Critical Periods For Network mentioning
confidence: 74%
“…Brain cells undergo massive elimination during two waves of apoptosis that take place from the embryonic stage E14 and between P6 and P10 in mice ( Figure 2 ; for review Wong and Marin, 2019 ). In contrast to previously reported cell-autonomous regulation of cell death (Southwell et al, 2012 ), new evidence suggests that specific patterns of postnatal network activity establish the onset, duration and extent of neuronal apoptosis (Blanquie et al, 2017 ; Denaxa et al, 2018 ; Priya et al, 2018 ; Wong et al, 2018 ; Duan et al, 2020 ). Recent work identified two molecular pathways guiding the selection process that determines neuron survival and sets the final composition of a neural network in the cerebral cortex: the calcium-dependent phosphatase Calcineurin, that translates the arrival of electrical activity into molecular cascades of cell survival (Priya et al, 2018 ), and the phosphatase tensin homolog protein (PTEN), that sets the clock for the death of the GABAergic interneurons in the absence of incoming activity from pyramidal neurons (Wong et al, 2018 ).…”
Section: Classical Critical Periods and Critical Periods For Network mentioning
confidence: 74%
“…Furthermore, GABAergic signaling is required for activity-dependent wiring of the developing cortex (Che et al, 2018;Duan et al, 2019;Marques-Smith et al, 2016;Modol et al, 2019;Oh et al, 2016;Tuncdemir et al, 2016). Here, we investigated how inhibitory signaling shapes spontaneous event patterning in V1 before eye opening.…”
Section: Introductionmentioning
confidence: 99%
“…Pcdh-γ C isoforms in young cIN could also be interacting with other Pcdhs expressed by pyramidal neurons and therefore explain the adjustment in cIN number that occurs as a function of pyramidal cell number (Wong et al 2018). Recent work has shown that coordinated activity of synaptically connected assemblies of cIN and pyramidal cells is essential for the survival of MGE-derived cIN (Duan et al 2020). It is possible that all or some of the Pcdh-γ C isoforms are required for cIN of the same age to find each other and form these assemblies.…”
Section: Discussionmentioning
confidence: 99%